A clinical case of cardiac arrhythmia and amiodarone-induced thyrotoxicosis in a patient with coronary heart disease - Kakorin, S. V.; Isaeva, I. V.; Voevodina, N. Y.; Mindzhiya, K. L.; Vorobieva, T. G.; Stogov, A. V. (Medical Council, 2016)
The article analyzes a clinical cases of cardiac arrhythmia and amiodarone-induced thyrotoxicosis (AIT) in a patient with coronary artery disease (CAD). The article discussed the causes of cardiac arrhythmia and the treatment approach for CAD based on coronary angiography (CAG), as well as the efficacy of revascularization by coronary artery bypass grafting. The importance of hormonal tests and thyroid ultrasound before routine CAG is considered, and at least once in 6 months during amiodarone therapy. Differential diagnosis to clarify the type of AIT is carried out, as type I AIT is treated with tireostatics, and type II AIT with glucocorticosteroids. Comorbidity of somatic diseases in cardiological practice is one of the most crucial prognostic factors defining the outcome of the underlying disease. The article considers the choice of treatment approach for patients with CAD based on clinical tests.